CONTENT ANALYSIS ON THE ENGLISH TEXTBOOK ENTITLED BAHASA INGGRIS SMA/MA KELAS X - Sihad Syale, Ari; Kamaluddin, Kamaluddin; Siam, Siam (Journal of Teaching English, 2019)
This research was accomplished to find out whether Bahasa Inggris textbook for Grade X fulfilled each criterion of textbook evaluation criteria based on Jahangard’s theory. The researcher used the qualitative analysis design. The data source was collected from Bahasa Inggris textbook for Grade X published by Pusat Kurikulum dan Perbukuan, Balitbang, Kemendikbud. The instrument of this study was a table of textbook evaluation criteria. The researcher collected the data by using checklist to evaluate the textbook and analyze the data shown by the checklist and make some interpretations, and finally describing the results from the assessment table. The result confirmed that only five of fourteen sub-criteria which did not be fulfilled, they are vocabulary section consists of list of words and their definition, each chapter should consist of four skills, there is a grammar presentation in each chapter and the words are correctly spelled. While the rest nine of sub-criteria were fulfilled. It was recommended to the teacher to be more critical and could cover the weaknesses of the textbook by various teaching style or find another reference outside the textbook. Keywords: Textbook, evaluation criteria.